Pengembangan e-LKPD Berbasis Attention, Relevance, Confidence, and Satisfaction Menggunakan Liveworksheets Pada Materi Kesetimbangan Ion dan pH Larutan Garam - R. Usman Rery; Herdini Herdini; Devyta Marinsi (Universitas Pendidikan Mandalika Mataram, 2022)
The development of ARCS-based E-LKPD using liveworksheets on the subject of ionic equilibrium and pH of salt solution aims to produce a valid E-LKPD and know the reactions of user responses. This study uses research and development (R&D) method with a 4D development model (Define, Design, Develop, Disseminate) which was carried out only until the Develop stage. The data collection instruments used were validation sheets and respondent questionnaires. The research subject were 3 students for one to one evaluation, 2 teachers and 20 students as respondents in limited trial from two schools at SMAN Pekanbaru. The results showed that the ARCS-based E-LKPD using liveworksheets was valid based on the assessment of the material and media validators with an average percentage score of 95.97% and 94.56%. The results of the questionnaire responses of teachers and students are in the very good criteria with an average percentage score of 90.27% and 80.87%. Thus, the ARCS-based E-LKPD using liveworksheets on the subject of ion equilibrium and pH of salt solutions is valid and can be used as learning materials in chemistry learning.